BIM-based Optimization of Placing Sequencing of A Concrete Gravity Dam - XU Xiaofeng; YU Hong; JIANG Kaiyun (Renmin Zhujiang)
The construction of concrete gravity dams is subject to various factors, of which the rational arrangement of the placing face significantly impacts the total duration. To seek an ideal duration under a variety of limitations, the BIM technology and Shell's sort are jointly applied in the visual simulation of the dam placement plan. A dam BIM model is built and stratified. The stratified dam block sequences are taken as the variable, and the placing intensity, vertical placing interval time, transverse placing interval time, maximum adjacent height difference, and flood control rule as constraints. The Shell's sort is then applied to find the optimal solution of the placing scheme under those constraints, a computer program was developed by the Revit API interface based on .Net framework and C# language. The visual simulation of the concrete-placement optimization sequencing process was achieved. According to the engineering application, the program can quickly obtain the optimal placing sequencing and total duration under different constraints. The finding is of great significance in guiding the mechanical equipment and can be applied to similar projects.